Coupled CFD-DEM simulation of progressive failure of tunnel face in sand - Zuyan Wang; Chuang Zhou; Yongkang Zhang; Weiyi Li; Yongjun Qin; Jiangu Qian (PLoS ONE, 2025)
Many studies have investigated tunnel face failure using the discrete element method (DEM). However, DEM simulations that incorporate water-soil interactions in tunnel face failure are still limited. In this study, the coupled CFD-DEM method is employed to simulate the progressive failure of the shield tunnel face in both saturated and dry sand. The dynamic mesh method is applied in the CFD component to accurately simulate the changes in the CFD domain due to the movement of the tunnel face. The excavation face is moved forward or backward at a uniform rate to simulate passive and active failure, respectively. The analysis focuses on progressive failure, ground surface displacement, tunnel face support forces, force chain distribution, and vertical stress distribution. Our results at both macro- and micro-scales reveal significant effects of soil-water interactions.